ANALYSIS OF THE ROLE OF THE CIREBON DISTRICT ATTORNEY'S OFFICE IN THE TERMINATION OF PROSECUTION BASED ON RESTORATIVE JUSTICE - Fahad Wiranata; Loevyta Nafishadita; Muhammad Dzaky Noer Raehan; Raissa Kemala Dewi; Rofiq Nurudin,; Salsabilla Putri Raihannanda; Siti Nurjanah (Ann Publisher, 2025)
Abstract: Background: The criminal law system in Indonesia continues to change to follow the community's demands for fair laws. One method that is getting more and more attention is restorative justice, which aims to solve criminal problems by rehabilitating communities, perpetrators, and victims rather than simply providing punishment. Aims. This research aims to better understand how the Cirebon District Attorney's Office implements the restorative justice process, its foundation, and the impacts and challenges faced in its implementation. Method: The methodology used is an Empirical law study using qualitative research parameters. Primary data is the main data, and secondary data functions as supporting data. Primary data can be obtained through interviews, and secondary data can be obtained through literature studies and interviews with relevant prosecutors who have applied Restorative Justice to handle a case. As a result, the research shows that the Cirebon District Attorney's Office has played an active role in implementing the dismissal of charges based on restorative justice in line with the Attorney General's Office Number 15 of 2020 guidelines. Conclusion and Implications. In practice, the prosecutor plays the role of a facilitator in mediation between the perpetrator and the victim, ensuring that a wise agreement is reached and fulfilling a sense of justice for all parties. However, the challenges include the lack of public understanding of restorative justice. In some cases, the victim or their family is reluctant to reconcile because they think stopping the prosecution will reduce the deterrent effect for the perpetrator. This is especially the case in cases of minor abuse, where the victim feels that the legal process should still be ongoing to provide lessons for the perpetrator.